Combining polarized Raman spectroscopy and micropillar compression to study microscale structure-property relationships in mineralized tissues. (1st January 2021) - Kochetkova, Tatiana; Peruzzi, Cinzia; Braun, Oliver; Overbeck, Jan; Maurya, Anjani K.; Neels, Antonia; Calame, Michel; Michler, Johann; Zysset, Philippe; Schwiedrzik, Jakob
Highlights: Development, calibration, and validation of a method for quantitative collagen fibril orientation estimation based on polarized Raman spectroscopy (qPRS). Micropillar compression experiments at the length scale of a single bone lamella under hydrated conditions combined with collagen orientation analysis. Elastic modulus and yield stress were found to be strongly affected by mineralized collagen fibril (MCF) orientation. Failure modes and post yield behavior of isolated bone lamellae in compression depend on MCF orientation with a transition between softening to hardening behavior at θ = 48 ∘ − 54 ∘ . Abstract: Bone is a natural composite possessing outstanding mechanical properties combined with a lightweight design. The key feature contributing to this unusual combination of properties is the bone hierarchical organization ranging from the nano- to the macro-scale. Bone anisotropic mechanical properties from two orthogonal planes (along and perpendicular to the main bone axis) have already been widely studied. In this work, we demonstrate the dependence of the microscale compressive mechanical properties on the angle between loading direction and the mineralized collagen fibril orientation in the range between 0° and 82°. For this, we calibrated polarized Raman spectroscopy for quantitative collagen fibril orientation determination and validated the method using widely used techniques (small angle X-ray scattering, micro-computed tomography). We then performed compression tests on bovine cortical bone micropillars with known mineralized collagen fibril angles. A strong dependence of the compressive micromechanical properties of bone on the fibril orientation was found with a high degree of anisotropy for both the elastic modulus ( E a / E t = 3.80 ) and the yield stress ( σ a y / σ t y = 2.54 ) . Moreover, the post-yield behavior was found to depend on the MCF orientation with a transition between softening to hardening behavior at approximately 50°. The combination of methods described in this work allows to reliably determine structure-property relationships of bone at the microscale, which may be used as a measure of bone quality. Graphical abstract: Image, graphical abstract